TiC-MgO composite: an X-ray transparent and machinable heating element in a multi-anvil high pressure apparatus. Issue 2 (2nd April 2020) - Xu, Fang; Xie, Longjian; Yoneda, Akira; Guignot, Nicolas; King, Andrew; Morard, Guillaume; Antonangeli, Daniele
ABSTRACT: TiC-MgO composite was developed as a heating element for X-ray study in the multi-anvil high pressure apparatus. We synthesized TiC-MgO blocks (50–70 wt.% of TiC) by compression in a cold isostatic press followed by baking in a gas flow furnace. Heaters of tubular shape were manufactured from the synthesized blocks either by lathe or numerically controlled milling machine. The so-produced heating elements have been proved to generate temperatures up to 2250 K at 10 GPa, condition where classical graphite heaters are not suitable anymore due to graphite-diamond transition. These new heaters have been successfully used for in situ X-ray radiography and diffraction measurements on liquid Fe alloys, exploiting excellent X-ray transparency.